Effect of Cu Nanoparticles on the Properties of PP-g-PHMG/PE Monofilament and Its Antifouling Application - Yue Wang; Feng Han; Wenwen Yu; Jiangao Shi; Aiyan Shu; Min Zhang (International Journal of Polymer Science)
The modified polyethylene monofilament was prepared by melt blending and spinning using polyethylene (PE), polypropylene-grafted poly(hexamethylene guanidine) (PP-g-PHMG), and Cu nanoparticles (CuNPs). The effect of CuNP content on the structure, mechanical properties, and antimicrobial properties of the monofilaments was studied. In addition, the antifouling property of fishing nets using the modified polyethylene monofilaments was evaluated. The results showed that CuNPs were dispersed homogeneously in the monofilament matrix as microaggregates. The initial increase in the tensile strength of monofilament was attributed to the mechanical restraint, whereas a decrease in the tensile properties at 1.0 wt% CuNP content was due to the predominant effect of a decrease in the total crystallinity. A bacteriostatic test showed that the monofilament had an obvious inhibitory effect on Staphylococcus aureus. Furthermore, coupon test results showed that PP-g-PHMG/PE/CuNP nanocomposite netting had lower weight gain than PP-g-PHMG/PE netting (23.6% reduction) because of the combined antibacterial effect of both PHMG and CuNP. Therefore, PP-g-PHMG/PE/CuNP monofilament has the potential to produce green and efficient antifouling fishing nets.